Primary intracranial malignant melanoma in an adolescent: case report and literature review - Golden, Nyoman; Kencana, I Gusti Ketut Agung Surya; Lauren, Christopher; Saputra, Angky; Japardi, Denny (Frontiers in Surgery, 2025)
Primary intracranial malignant melanoma (PIMM) is an exceedingly rare central nervous system tumor, accounting for only 1% of melanoma cases and 0.07% of primary CNS tumors, with limited documentation in adolescents. This case report describes an 18-year-old male who presented with a seizure, marking the onset of his symptoms. Following an emergency assessment, MRI identified a heterogeneous mass in the right parasagittal frontal region, initially misdiagnosed as a cystic meningioma. A craniotomy allowed for total tumor resection, and histopathological analysis revealed a malignant melanoma characterized by neoplastic cells with pronounced nuclear pleomorphism and significant mitotic activity. Postoperative evaluations, including a PET scan, confirmed no extracranial melanoma, affirming the diagnosis of primary CNS melanoma. The patient demonstrated no neurological deficits or seizures one year post-surgery and was managed with adjuvant radiotherapy. This report emphasizes the necessity of considering PIMM in differential diagnoses for seizures in young patients and highlights the importance of comprehensive diagnostic evaluations, including MRI and histopathology, in rare cases. Additionally, the findings underscore the critical role of complete surgical resection in improving outcomes, with adjuvant therapies potentially enhancing long-term management and surveillance. As PIMM presents with nonspecific symptoms, awareness among clinicians is essential for early detection and appropriate intervention, warranting further research to develop standardized treatment protocols and enhance understanding of this rare tumor's pathophysiology.